Regular physical activity moderates the adverse impact of type 2 diabetes on brain atrophy independently from HbA1c - Moreno, Carolina; d’Almeida, Otília C.; Gomes, Leonor; Paiva, Isabel; Castelo-Branco, Miguel (Frontiers in Endocrinology, 2023)
Objective Brain atrophy has been consistently associated with type 2 diabetes, beginning in early stages of dysglycemia, independently from micro and macrovascular complications. On the contrary, physical activity relates with larger brain volumes. Our aim is to assess the influence of regular physical activity on brain volumes in people with type 2 diabetes. Methods A cross-sectional multimodal evaluation with 3T MRI was performed on 170 individuals: 85 individuals with type 2 diabetes and 85 controls. They underwent clinical examination, blood sampling and 3T MRI. Brain volumes (mm3) were estimated using FreeSurfer 7. Physical activity duration was self-reported by the participants as the number of hours of physical activity per week for at least the previous 6 months. Statistical analysis was performed with IBM SPSS 27. Results People with type 2 diabetes had significantly lower cortical and subcortical volumes, adjusted for age and individual intracranial volume, comparing to controls. Regression analysis showed that within type 2 diabetes group, lower gray matter volumes were associated with lesser physical activity duration (hours/week), independently from HbA1c. Moreover, there were significant moderate positive correlations between regular physical activity duration and gray matter volumes of cortical and subcortical subregions, specifically in the diabetes group. Conclusions This study reveals a putative beneficial effect of regular physical activity independently of glycemic control, as assessed by HbA1c, moderating the negative impact of type 2 diabetes in the brain.